Local influence of cell viability on stretch-induced permeability of alveolar epithelial cell monolayers - Song, MJ (Cell Mol Bioeng, 2015)
Ventilator induced lung injury (VILI), often attributed to over-distension of the alveolar epithelial cell layer, can trigger loss of barrier function. Alveolar epithelial cell monolayers can be used as an idealized in vitro model of the pulmonary epithelium, with cell death and tight junction disruption and permeability employed to estimate stretch-induced changes in barrier function. We adapted a method published for vascular endothelial permeability, compare its sensitivity with our previously published method, and determine the relationship between breeches in barrier properties after stretch and regions of cell death After 4-5 days in culture, primary rat alveolar epithelial cells seeded on plasma treated polydimethylsiloxane membrane coated with biotin-labeled fibronectin, or fibronectin alone were stretched in the presence of FITC-tagged streptavidin (biotin-labeled membrane) or BODIPY-ouabain. We found that the FITC-labeling method was a more sensitive indicator of permeability disruption, with significantly larger positively stained areas visible in the presence of stretch and with ATP production inhibitor Antimycin-A. Triple-stained images with Hoescht (nuclei), Ethidium Homodimer (EthD, damaged cell nuclei) and FITC (permeable regions) were used to determine that within permeable regions intact cells were positioned closer to damaged cells than in non-permeable regions. We concluded that local cell death may be an important contributor to barrier integrity.